(untitled) (Tzintzun, Revista de Estudios Históricos, 2022)
The correspondents of the Peruvian newspapers that covered the alternatives of the naval campaign of the War of the Pacific (April-October 1879) contributed to satisfy the information needs of public opinion. In addition, they allowed the creation of representations and imaginaries linked to the archetypes of behavior and patriotic virtues of the Peruvians, as well as the construction of the Chilean otherness. These writings collaborated in delineating the contemporary and future interpretative canon of the conflict.